Menyelusuri Makna Tersembunyi: Identifikasi Asbāb Al-Nuzul Dan Implikasinya Dalam Tafsir Al-Qur'an - Bariroh, Roikhatul Jannatul; Nimah, Rodhotun (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2024)
Asbab al Nuzul has been widely used by commentators to understand the verses of the Qur'an. So it is necessary for a commentator to be able to analyze the validity of the Asbāb al Nuzul in the Qur'an. Research with this descriptive analysis method yields an understanding Asbāb al-nuzul is a notification or news about the revelation of a verse either regarding an incident or a question, namely when an event occurs and the Qur'an is revealed about it. Second, when Rasulullah SAW. asked about something and sent down the Qur'an which explains the law. To find Asbāb al-nuzul verse, it is necessary to pay attention to the first, the revelation is based on the validity of the history of the Prophet Muhammad. or to friends. Second, if the history is taken before it is transmitted to a friend, if it is from tabi'in, then it is considered marfu' but mursal, and it can also be accepted if the sanad is correct. Third, many interpreters mentioned the reason for the revelation of the verse with a different way of reference, namely by looking at its expression. The difference in the number of verses in the Qur'an is that there are seven well-known opinions mentioned in the book al-Bayᾱn fῑ 'adῑ al-Qur'ᾱn. Namely Al-Madanῑ al-Awwal: In the kufic narrations of Madina experts there are 6,217 verses. While in the history of ahlul Basrah there are 6,214 verses, Al-Madanῑ al-Akhῑr: 6,214 verses, Al-Makkῑ: 6,210 verses, Al-Baṣrῑ: 6,204 verses, Al-Dimashqῑ: 6,227 and it says 6226 verses, Al-Ḥamṣῑ: 6,232 verses, Al-Kūfῑ : 6,236 verses. According to al-Suyūťi there are 591 verses, and according to Al Wahidi there are 715 verses that have Asbāb al-Nuzūl. If disensenkan around 9-10%. So that it can be concluded that not all verses in the Qur'an have a cause for Nuzul, even though they are considered important they cannot arbitrarily take events at the time of the Prophet to serve as the cause for the revelation of a verse.